How a fungus can control ant behaviour. (Research'eu results magazine)
One of the most graphic examples of parasites controlling behaviour is the manipulation of carpenter ants infected by the fungus Orphiocordyceps unilateralis. The parasite, which has recently been the subject of an EU-funded study, causes its host to bite into vegetation before dying; a trait that is essential to the fungi's lifecycle.